2014
DOI: 10.1371/journal.pone.0107391
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ginseng (The Genus Panax) on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Controlled Clinical Trials

Abstract: ImportanceDespite the widespread use of ginseng in the management of diabetes, supporting evidence of its anti-hyperglycemic efficacy is limited, necessitating the need for evidence-based recommendations for the potential inclusion of ginseng in diabetes management.ObjectiveTo elucidate the effect of ginseng on glycemic control in a systematic review and meta-analysis of randomized controlled trials in people with and without diabetes.Data sourcesMEDLINE, EMBASE, CINAHL and the Cochrane Library (through July 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 32 publications
1
65
0
Order By: Relevance
“…In a clinical setting, Panax ginseng has been shown to exert positive effects on glucose metabolism reflected by an improved glucose tolerance (Shergis, Zhang, Zhou, & Xue, 2013). A meta-analysis of 16 randomized controlled trials of moderate duration (≥30 days) assessing the glycaemic effects of ginseng in diabetic patients have found that ginseng modestly yet significantly improved fasting blood glucose in people with and without diabetes (Shishtar et al, 2014). It must be noted that most of these studies were of short duration (67% trialsb12wks), and that participants included also have a relatively stable glycaemic control (median HbA1c non-diabetes=5.4% [2 trials]; median HbA1c diabetes=7.1% [7 trials]).…”
Section: The Use Of Natural Products and Complementary Medicinesmentioning
confidence: 99%
“…In a clinical setting, Panax ginseng has been shown to exert positive effects on glucose metabolism reflected by an improved glucose tolerance (Shergis, Zhang, Zhou, & Xue, 2013). A meta-analysis of 16 randomized controlled trials of moderate duration (≥30 days) assessing the glycaemic effects of ginseng in diabetic patients have found that ginseng modestly yet significantly improved fasting blood glucose in people with and without diabetes (Shishtar et al, 2014). It must be noted that most of these studies were of short duration (67% trialsb12wks), and that participants included also have a relatively stable glycaemic control (median HbA1c non-diabetes=5.4% [2 trials]; median HbA1c diabetes=7.1% [7 trials]).…”
Section: The Use Of Natural Products and Complementary Medicinesmentioning
confidence: 99%
“…Positive results were obtained with P. quinquefolius e P. ginseng in the metabolic regulation of glucose in subjects with or without diabetes mellitus. This was the aim of a systematic review that evaluated 16 clinical studies, 9 of which recruited 339 subjects with type 1 and type 2 diabetes mellitus and 7 enrolled 431 subjects without diabetes mellitus (Shishtar et al, 2014). Among these 16 clinical trials, 11 used parallel and 5 used crossover designs, and thirteen had placebo as comparator (Shishtar et al, 2014).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…, ), endocrine system diseases (Shishtar etal. , ), inflammation (Lee etal. , ) and cancer (Wang etal.…”
Section: Introductionmentioning
confidence: 99%